2020
DOI: 10.1002/ccd.29248
|View full text |Cite
|
Sign up to set email alerts
|

Acute and medium term results of balloon expandable stent placement in the transverse arch—a multicenter pediatric interventional cardiology early career society study

Abstract: Objectives and Background: Coarctation of the aorta represents 5-8% of all congenital heart disease. Although balloon expandable stents provide an established treatment option for native or recurrent coarctation, outcomes from transverse arch (TAO) stenting, including resolution of hypertension have not been well studied. This study aims to evaluate immediate and midterm results of TAO stenting in a multicenter retrospective cohort. Methods: TAO stenting was defined as stent placement traversing any head and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Similar to findings in other studies, we observed a statistically significant decrease in systemic blood pressure, pressure gradient through the aorta, and an increase in TAA diameter. [5,9,10] In our study, all patients were hypertensive before the TAA stenting procedure. However, the proportion of normotensive patients increased following stent implantation, with eight (44%) of 18 patients achieving a normotensive state during the follow-up period (Figure 6).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Similar to findings in other studies, we observed a statistically significant decrease in systemic blood pressure, pressure gradient through the aorta, and an increase in TAA diameter. [5,9,10] In our study, all patients were hypertensive before the TAA stenting procedure. However, the proportion of normotensive patients increased following stent implantation, with eight (44%) of 18 patients achieving a normotensive state during the follow-up period (Figure 6).…”
Section: Discussionmentioning
confidence: 94%
“…There are few studies on TAA stenting in the literature. [5,[9][10][11] The present study comprehensively evaluated this intervention from a technical standpoint and its effect on hypertension. Stent implantation was successfully performed in all patients, with no reported mortality or major complications during the acute period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evolution of interventional techniques for management of coarctation of the aorta requires a separate review of this evolving field but we highlight a few recent developments. With increasing experience with interventional techniques, they have been applied to novel patient groups including balloon angioplasty for low-birth-weight premature infants [37 ▪ ], balloon angioplasty using axillary access for critically ill newborns [38 ▪ ], stenting for selected children under 3 months of age [39 ▪ ], and stenting for arch hypoplasia [40 ▪ ,41 ▪ ]. There are promising results of stent implantation being performed in younger children less than 12 kg [42] and less than 20 kg [43].…”
Section: Percutaneous Interventionsmentioning
confidence: 99%